2010
DOI: 10.3340/jkns.2010.48.1.46
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Pedicle Screw-Rod System for the Posterior Fixation in Cervico-Thoracic Junction

Abstract: Objective : In cervico-thoracic junction (CTJ), the use of strong fixation device such as pedicle screw-rod system is often required. Purpose of this study is to analyze the anatomical features of C7 and T1 pedicles related to screw insertion and to evaluate the safety of pedicle screw insertion at these levels. Methods : Nineteen patients underwent posterior CTJ fixation with C7 and/or T1 included in fixation levels. Seventeen patients had tumorous conditions and two with post-laminectomy kyphosis. The anatom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…58 It is no wonder that this transition zone where the lordotic cervical spine blends to the kyphotic curvature of the thoracic spine is a structurally critical area that is susceptible to many kinds of insults. 13,49 Furthermore, Cho et al found that lower cervical laminae are thinner and weaker compared with upper thoracic vertebrae, again demonstrating another anatomical point of inflection that can be exploited by traumatic or repetitive motion. 13,43 Within the surgical literature for CSM, fusions ending at C-7 raise concern about instability and adjacentsegment disease; 26,31 our findings that listhesis at the CTJ correlates with a worse mJOA score in CSM suggest that stability between C-7 and T-1 is related to myelopathy severity.…”
Section: Focal Abnormalitiesmentioning
confidence: 99%
“…58 It is no wonder that this transition zone where the lordotic cervical spine blends to the kyphotic curvature of the thoracic spine is a structurally critical area that is susceptible to many kinds of insults. 13,49 Furthermore, Cho et al found that lower cervical laminae are thinner and weaker compared with upper thoracic vertebrae, again demonstrating another anatomical point of inflection that can be exploited by traumatic or repetitive motion. 13,43 Within the surgical literature for CSM, fusions ending at C-7 raise concern about instability and adjacentsegment disease; 26,31 our findings that listhesis at the CTJ correlates with a worse mJOA score in CSM suggest that stability between C-7 and T-1 is related to myelopathy severity.…”
Section: Focal Abnormalitiesmentioning
confidence: 99%
“…Original Study C7 intra-laminar screws for complex cervicothoracic spine surgery-a case series similar results obtained with thoracic pedicle screw fixation (2)(3)(4). Of note, C7 has been successfully used as an anchor point using its lateral masses (5) and pedicles (6,7), although in many patients the lateral mass of C7 may be small, and pedicle fixation can be technically demanding and require a wide exposure. Higher level cervical pedicle screw fixation has been well described but is also technically challenging with greater consequences of pedicle breaches (8).…”
Section: Introductionmentioning
confidence: 80%
“…[ 16 17 18 ] According to the anthropometric data the “safest” vertebrae for SCPS are C6 and C7, due to the larger diameter of pedicles,[ 1 3 11 16 17 18 19 ] besides, more than 95% of C7 vertebrae do not contain a vertebral artery. [ 20 ] “Most dangerous” vertebrae for SCPS are C3–C5, the risk of neurovascular injury is much higher due to smaller diameter and steep slope of axis of the pedicle. [ 1 3 11 16 17 18 19 ] In general, the method of SCPS insertion is recommended for application by experienced surgeons.…”
Section: Discussionmentioning
confidence: 99%